Política cambial brasileira e seus efeitos nas exportações paraenses: 1990 - 2003 - MAGALHÃES, Marco Aurélio Dias (Universidade Federal do Pará, 2011)
The main objective of this paper is to analyze the effects that the exchange brasilian policy has promoted in the F.O.B. exportation of bauxite, primary aluminium, iron ore and kaolin. For so, it is developed an econometric model, Nerlove Partial Adjustment model, trying to evalvate the patterns of reaction of the exportations at short and long terms. The used data are quarterly and cover the period of 1990 through 2003. The regressions were estimated through the Ordinary Minimum Squares (OMS) method. The variables elected as explanatory ones were the Brazilian effective real rate of exchange, the world revenue, the production capacity of the Brazilian industry, the gross internal product of the Brazilian industry and a dummy variable (which captures the influence of Kandirs law). The results of such regressions have shown that: exportations are relatively sensible to the growth of the Brazilian and worlds economics; and, the Brazilian effective real rate of exchange (proxy of the exchange policy) has produced important effects in the evolution of exportations of Parás oremetallurgical sector.